Mediation in Lithuanian Criminal Jurisprudence - Liesis, Mantas; Michailovič, Ilona (Kriminologijos studijos, 2018)
[only abstract in English; full article and abstract in Lithuanian]The article discusses mediation in Lithuanian criminal and administrative infringement cases. The challenges of mediation are discussed from the perspective of both the first instance judge and leading scholar in the field of mediation in Lithuania. The article analyzes the practical issues of mediation, questions the legal status of mediation in Lithuanian criminal jurisprudence and shows a good practice of mediation in criminal and administrative infringement cases.Mediation is not the court and does not substitute the court; the final decision is made by the court. Mediation could allow both parties to reach an agreement. However, the victim and the culprit do not always reach for an agreement. It is a beneficial practice in both ways. With the help of a mediator, parties learn how to discuss and hear the other side. It aids in coexisting in non-conflict ways in the future. Foreign experience reveals the most important doubts in the process of mediation that both the victim and the culprit face. The society lacks information on mediation. A high priority should be given for increasing the awareness of the benefits of mediation. Judges represent an authoritative power of the state and should use it in the reconciliation of conflicting parties.Lithuanian criminal justice lacks legislation in the field of mediation; however, mediation is de facto possible if the judge is active. Also, mediators who work at the institutions of probation help to legitimize the institute of mediation.
Keywords: none